2020
DOI: 10.4049/jimmunol.1901210
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of TLR Signaling by BCAP Requires Dimerization of Its DBB Domain

Abstract: The B cell adaptor protein (BCAP) is a multimodular regulator of inflammatory signaling in diverse immune system cells. BCAP couples TLR signaling to phosphoinositide metabolism and inhibits MyD88-directed signal transduction. BCAP is recruited to the TLR signalosome forming multitypic interactions with the MAL and MyD88 signaling adaptors. In this study, we show that indirect dimerization of BCAP TIR is required for negative regulation of TLR signaling. This regulation is mediated by a transcription factor Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…By focusing on the two pathways involved in cGAMP and LPS signaling, the only gene with significantly altered expression in D2I fibroblast was PIK3AP1 , coding BCAP, an adaptor protein coupling various receptors, like B cell receptor and Toll-like receptors, to PI3K [ 35 ]. BCAP is a major modulator of TLR signaling, downregulating NF-kB activation [ 36 ] and favoring type I IFN induction [ 21 ]. Very recent data showed that activation of the STING-Lyn pathway leads to PIK3AP1 hyper-expression, which can be relevant to the development of SLE in lupus prone mice, thus adding substance to our findings [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…By focusing on the two pathways involved in cGAMP and LPS signaling, the only gene with significantly altered expression in D2I fibroblast was PIK3AP1 , coding BCAP, an adaptor protein coupling various receptors, like B cell receptor and Toll-like receptors, to PI3K [ 35 ]. BCAP is a major modulator of TLR signaling, downregulating NF-kB activation [ 36 ] and favoring type I IFN induction [ 21 ]. Very recent data showed that activation of the STING-Lyn pathway leads to PIK3AP1 hyper-expression, which can be relevant to the development of SLE in lupus prone mice, thus adding substance to our findings [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…BCAP is a dimeric protein and its oligomerization depends on its ANK (ankyrin repeat) and DBB (Dof/BANK1/BCAP) domains. A recently concluded study clearly defines the importance of DBB domain in dimerization and its role in TIRAP-BCAP interaction ( 39 ). The monomeric BCAP, though fails to negatively regulate the TLR signaling suggesting that only domain dimerization drives the negative response.…”
Section: Tirap and Phosphatidylinositol 3′-kinase P85 And B-cell Adaptor For Phosphoinositide 3-kinase (Bcap)mentioning
confidence: 99%
“…Such a filament could be disrupted by dimeric, and not monomeric, BCAP. Another angle suggest BCAP phosphoinositide metabolism, which cleaves PIP2 to DAG and IP3 and hence deprives TIRAP for its membrane anchor required for TLR signaling ( 39 ). Overall, the BCAP association mainly with TIRAP and p85α provides novel directions for regulatory pathways in inflammation.…”
Section: Tirap and Phosphatidylinositol 3′-kinase P85 And B-cell Adaptor For Phosphoinositide 3-kinase (Bcap)mentioning
confidence: 99%
“…When MAMPs bind to the ECD, the TIR domain of each TLR recruits its respective adapters. In mammals, there are a total of seven adapters involved, namely MyD88, MAL, TRIF, TRAM, SARM, BCAP, and SCIMP [ 22 , 27 , 32 , 36 ]. These adaptors then deliver signals downstream to activate either the NF-κB signaling pathway or the IFN signaling pathway [ 16 , 35 , 57 ].…”
Section: Introductionmentioning
confidence: 99%